Understanding the content of crimes against humanity: Tracing its historical evolution from the Nuremberg Charter to the Rome Statute - Brian Dube (Academic Journals (A J), 2023)
The term ‘crimes against humanity’ has been widely used by different people to mean different things.The media has referred the term to include a variety of contemporary political events that they have reported on. The media practitioners and social workers have used the term loosely to refer to situations where the governments or any other people holding power, authority or influence have done any wrong. Politicians and political scientists deploy the term while referring to unacceptable and unfair activities in the political field. To International law scholars, the term has been used to refer to a specific crime under international criminal law, as distinguished from Genocide and War Crimes. This paper traces how crimes against humanity as a category of international crimes emerged and its essential requirements and how courts and institutions have developed and interpreted it, since the term crimes against humanity has acquired both a legal as well as socio-political perspective.